ANALYSIS OF PRESUPPOSITION IN TAYLOR SWIFT’s NEW YORK UNIVERSITY HOLDS 188th COMMENCEMENT - Siahaan, Feratiwi Christina; Silalahi, Charles David Marudut (Cahaya Ilmu Bangsa Institute, 2025)
In Taylor Swift’s speech given at New York University in 2022 for her graduation ceremony, Taylor Swift used several presuppositions in her speech. Of course, presuppositions, as assumptions inherent to the emotional approach, are crucial to determining the feeling and argumentation of the message Taylor Swift conveys to the audience. Through this analysis, the researcher will identify and explain how these presuppositions can build an emotional connection with the audience and at the same time empower the graduates through her presuppositions.